Retention and release properties of cinnamon essential oil in antimicrobial films based on chitosan and gum arabic. (November 2018) - Xu, Tian; Gao, ChengCheng; Yang, Yuling; Shen, Xinchun; Huang, Meigui; Liu, Shaowei; Tang, Xiaozhi
Abstract: Film-forming dispersions and films based on chitosan (CS), gum arabic (GA) and cinnamon essential oil (CEO) were prepared. The influence of different mass ratios of CS/GA on properties of film-forming dispersions and antimicrobial activities of films were characterized. Especially, the effects of CS/GA ratios on the retention and release properties of CEO were quantified. Results showed that a lower ζ-potential and smaller particle size were obtained with increasing GA ratios from 1:0 to 1:2, indicating electrostatic interactions occurred between CS and GA. Fluorescence microscopy results demonstrated higher retention and less aggregation of CEO in the composite films, meaning increased compatibility of the multiphased system when proportions of GA increased from 1:0 to 1:2. The loss of CEO in fresh films (day 0) was reduced from 54.56% to 34.23% and its retention time during storage was increased up to 15 days. TGA analysis further verified higher retention of CEO during heating. In addition, a delayed and sustained release of CEO was observed, thus enhancing antimicrobial activities of composite films. However, when the ratio of CS/GA was at 1: 4, the electrostatic interactions between CS and GA tended to reach maximum, leading to the formation of insoluble complexes, which was not beneficial for the retention and release properties of CEO in composite films. Graphical abstract: Image Highlights: Electrostatic interactions and emulsified CEO improved multicomponent compatibility. Higher stability and retention of CEO during storage and heating were presented. A delayed and sustained release of CEO enhanced antibacterial effects on E. Coli. Maximum interactions between CS and GA was not beneficial for film properties.